MOTIVASI AUSTRALIA MENDUKUNG PROGRAM THE CORAL TRIANGLE DI KAWASAN ASIA PASIFIK TAHUN 2008 – 2012 - Oki Satria; Syafri Harto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The Asia-Pacific's Coral Triangle is defined by its extremely high marinebiodiversity. Over one hundred million people living in its coastal zones use thisbiodiversity to support their livelihoods. Hundreds of millions more derive nutritious fooddirectly from the region′s marine resources and through local, regional and global trade.Biodiversity and its values to society are threatened by demographic and habitat change,rising demand, intensive harvesting and climate change. In partnership withinternational conservation organizations and development funders, the governments ofthe region′s six countries have come together to develop the Coral Triangle Initiative(CTI) on Coral Reefs, Fisheries and Food Security. The focus of this research isAustralia role on CTI, related to the fact that Australia is not of the part CT state, butcommited very actively and maximum for the CTI - CFF. This research uses InternationalOrganization theory which has been revealed by Peter J. Katzenstein, Robert Keohaneand Stephen D. Krasner. This research is qualitative research which is used by libraryobservation. The result of this research prove that full commitment Australia in CTI –CFF is motivated by desire to 1) spread and strengther Australia hegemon in Pacificregion; 2) enchancing and exploring global image in marine research (megadiversity);3) maintain the ecosystme in the Great Barrier Reef.Keywords: CTI-CFF, Coral Triangle, Australia in CTI – CFF, Megadiversity.